2011
DOI: 10.1093/nar/gkr526
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of TAR RNA-DNA annealing in the absence and presence of HIV-1 nucleocapsid protein

Abstract: Annealing of the TAR RNA hairpin to the cTAR DNA hairpin is required for the minus-strand transfer step of HIV-1 reverse transcription. HIV-1 nucleocapsid protein (NC) plays a crucial role by facilitating annealing of the complementary hairpins. To gain insight into the mechanism of NC-mediated TAR RNA–DNA annealing, we used structural probes (nucleases and potassium permanganate), gel retardation assays, fluorescence anisotropy and cTAR mutants under conditions allowing strand transfer. In the absence of NC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 69 publications
6
23
0
Order By: Relevance
“…As previously reported (29), KMnO 4 is expected to interact with the nucleobases of unpaired thymine residues that interact with the N-terminal zinc finger of NC. Indeed, a close examination of the structures of the NC⅐DNA complexes (53,54) shows that the 5,6-double bond of the nucleobase thymine in these complexes is accessible to KMnO 4 .…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…As previously reported (29), KMnO 4 is expected to interact with the nucleobases of unpaired thymine residues that interact with the N-terminal zinc finger of NC. Indeed, a close examination of the structures of the NC⅐DNA complexes (53,54) shows that the 5,6-double bond of the nucleobase thymine in these complexes is accessible to KMnO 4 .…”
Section: Resultssupporting
confidence: 62%
“…Our results show that the cpoly(A) and the cTAR hairpins are formed in the full-length ssDNA. Previous studies showed that short DNAs corresponding to the cTAR sequence (55 or 59 nucleotides) adopt two alternative hairpin conformations in the absence of NC: the closed form and the partially open Y form (20,27,29). Interestingly, our probing data indicate that the cTAR sequence in ssDNA adopts the partially open Y form but not the closed form (conformer 1 in Fig.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In addition, NC binding to TAR RNA and its role in destabilizing the hairpin during the minus-strand transfer step of reverse transcription is well established (Kanevsky et al 2005(Kanevsky et al , 2011Vo et al 2009b;Levin et al 2010;Heng et al 2012). In an HIV-1 variant that does not depend on Tat-TAR interaction for transcription activation, TAR is not required for gRNA packaging (Das et al 2007), but TAR destabilization leads to aberrant RNA dimerization and packaging (Das et al 2012).…”
Section: Discussionmentioning
confidence: 99%